Does the market discipline banks? New evidence from the regulatory capital mix - Adam B. Ashcraft (Federal Reserve Bank of New York, 2006)
Although bank capital regulation permits a bank to choose freely between equity and subordinated debt to meet capital requirements, lenders and investors view debt and equity as imperfect substitutes. It follows that the mix of debt in regulatory capital should isolate the role that the market plays in disciplining banks. I document that since the Federal Deposit Insurance Corporation Improvement Act of 1991 (FDICIA) reduced the ability of the FDIC to absorb losses of subordinated debt investors, the mix of debt has had a positive effect on the future outcomes of distressed banks, as if the presence of debt investors has worked to limit moral hazard. To mitigate concerns about selection, I use the variation across banks in the mix of debt in capital generated by cross-state variation in state corporate income tax rates. Interestingly, instrumental variables (IV) estimates document that selection problems are indeed important, but suggest that the benefits of subordinated debt are even larger. I conclude that the market may play a useful direct role in regulating banks.
Keywords: G21; G28; G32; G38; 330; bank capital regulation; market discipline; subordinated debt; Basler Akkord; USA